The Effect of Brown Seaweed (Sargassum sp.) Extract on Apoptosis Process in Breast Cancer – A Literature Review - Ismylatifa Devi; Diah Purwaningsari; Nita Pranitasari; HerinSetianingsih (Indian Journal of Forensic Medicine & Toxicology, 2021)
Breast cancer was one of the most common types of cancer in women and the major cause of death. Chemotherapy in breast cancer caused toxicity to the normal cells, resistance to the drugs, and several other side effects. Seaweed had many functional compounds that could be used as adjuvant therapy in breast cancer because of its anti-cancer properties called the proapoptotic agent. These compounds were fucoidan, phloroglucinol, and fucoxanthin. Their proapoptotic mechanisms shown by the journal were through increasing proapoptotic protein expression, decreasing antiapoptotic protein expression, inducing oxidative stress production on the cancer cell, and inhibiting the PI3K pathway. This review concludes that the brown seaweed (Sargassum sp.), which contains fucoidan, phloroglucinol, and fucoxanthin, could increase breast cancer cells’ apoptotic process.